PERAN GURU DALAM MENGOPTIMALKAN PAPAN INTERAKTIF DIGITAL SEBAGAI MEDIA PEMBELAJARAN OPERASI HITUNG BILANGAN BULAT PADA MATA PELAJARAN MATEMATIKA KELAS IV DI SDN GIRIREJO 1 - Atik Khusnawati; Rahayu Retnaningsih; Sukiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to describe the role of teachers in optimizing the use of digital interactive whiteboards as learning media for integer arithmetic operations in Grade IV mathematics at SDN Girirejo 1. The background of this research is the need for innovative digital media to support students’ understanding of abstract mathematical concepts, particularly integer operations, as well as the crucial role of teachers in integrating technology effectively into classroom instruction. This research employed a qualitative descriptive approach. The study was conducted in January 2026 at SDN Girirejo 1, Tempuran District, Magelang Regency, involving 18 fourth-grade students and one classroom teacher as research participants. Data were collected through classroom observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that teachers play a significant role in optimizing digital interactive whiteboards through careful lesson planning, interactive implementation of learning activities, and reflective evaluation of learning outcomes. The use of digital interactive whiteboards helps increase students’ learning motivation, engagement, and conceptual understanding of integer arithmetic operations when supported by appropriate pedagogical strategies. However, the study also found several challenges, including limited teacher proficiency in utilizing all interactive features and time constraints during classroom activities. Overall, the optimization of digital interactive whiteboards in mathematics learning depends not only on the availability of technology but also on the teacher’s pedagogical competence and creativity in designing meaningful learning experiences. Keywords: teacher role, digital interactive whiteboard, mathematics learning, integer arithmetic operations.